2007
DOI: 10.1521/pedi.2007.21.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks in Borderline Personality Disorder

Abstract: The interpersonal dysfunction that characterizes borderline personality disorder (BPD) has generally been studied using broad global measures, leading to a lack of precision. We report on a novel methodology using social network analysis (SNA) to quantify interactions with others in the patient's social world. We assessed the social networks of 22 clinical patients, diagnosed with either BPD (N = 11) or no personality disorder (No PD; N = 11). The social networks of patients with BPD contained a greater number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 3 publications
6
78
0
Order By: Relevance
“…It may be that the increased interpersonal aggression associated with BPD (Lejuez et al, 2003) results in damage to close, familiar interpersonal relationships, leaving those with high BPD symptoms without the emotion regulation support that would ordinarily be available in these types of relationships. Similarly, Clifton et al (2007) found that individuals with BPD had the most confl ictual relationships with those who were closest to them in their social networks. If this is the case, making choices of novel partners might be related to attending to emotion regulation goals.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It may be that the increased interpersonal aggression associated with BPD (Lejuez et al, 2003) results in damage to close, familiar interpersonal relationships, leaving those with high BPD symptoms without the emotion regulation support that would ordinarily be available in these types of relationships. Similarly, Clifton et al (2007) found that individuals with BPD had the most confl ictual relationships with those who were closest to them in their social networks. If this is the case, making choices of novel partners might be related to attending to emotion regulation goals.…”
Section: Discussionmentioning
confidence: 86%
“…Clifton, Pilkonis, and McCarty (2007) found that although the social networks of individuals with BPD were not globally different from those without a personality disorder, individuals with BPD had a higher number of former romantic partners in their social networks and reported a higher frequency of stopping communication with members of their social network compared to those without Axis II disorders. Additionally, using social interaction diaries, Stepp, Pilkonis, Yaggi, Morse, and Feske (2009) found that individuals with BPD had the same number of interactions with romantic partners, family members, friends, acquaintances, and strangers as individuals with other Axis II disorders and those with only Axis I disorders.…”
Section: Bpd and Interpersonal Functioningmentioning
confidence: 86%
See 1 more Smart Citation
“…BPD is associated with lower marital satisfaction, high levels of relational aggression, and frequent episodes of breakups and reconciliation (Bouchard, Sabourin, Lussier, & Villeneuve, 2009). In addition, those with BPD maintain highly unstable social networks, with a high frequency of changing relationships and terminated relationships (Clifton, Pilkonis, & McCarty, 2007). These interpersonal disturbances are also relevant to other symptoms and behaviors that are problematic in BPD.…”
mentioning
confidence: 99%
“…Although there are likely a number of factors involved in the transmission of risk from mothers with BP pathology to their children (e.g., shared biological vulnerabilities, co-occurring matemal psychopathology, genetics), one factor that holds particular promise is matemal parenting behaviors and the emerging pattem of mother-infant interactions. 907 Indeed, the prominent relationship instability in BPD (Gunderson, 2007) is just as likely to influence motherinfant relationships as it is to influence the adult social and romantic relationships that have been the primary focus of BPD researchers to date (Clifton, Pilkonis, & McCarty, 2007). Moreover, although past research examining motherinfant interactions among women with BPD has emphasized the relevance of BPD features related to insecure attachment and dismpted object relations to these interactions (Crandell, Patrick, & Hobson, 2003;Hobson et al, 2005), the significant emotion dysregulation in this disorder (Koenigsberg et al, 2009;Linehan, 1993) is also likely to infiuence the ways in which mothers interact with and respond to their infants.…”
mentioning
confidence: 99%